UJI AKTIVITAS PENGANGKAPAN RADIKAL 2,2-DIFENIL-1-PIKRILHIDRAZIL (DPPH) PIGMENT BAKTERIAL SIMBION DARI SARGASSUM POLYCYTRUM - Lia Kusmita; Sri Achadi Nugraheni; Handung Nuryadi (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
Carotenoids are pigments that are found in plants, animals, microorganisms and humans. The pigment has many functions, one of which is as an antioxidant. There have been many studies of carotenoids in plants, but the types of carotenoids in bacteria is very rarely observed when the potential is not lost. The ability of marine bacteria is well known to produce carotenoids. Bacterial symbionts associated with Sargassum polycytrum can produce neoxanthin. This research will test the antioxidant activity by DPPH method on bacterial symbionts pigment extracts as compared with extracts of S. polycytrum. Based on the results obtained IC50 of 3.01 ± 2350 ppm was obtain for extract pigments S. polycytrum, 645 ± 2.11 ppm for pigment extract bacterial symbionts, and 564 ± 2.26 ppm for β-carotene as a comparison.